Exposure to soiled bedding reduces abnormal repetitive behaviors in mice - Müller, Karin; Lengheimer, Theresia; Kral-Pointner, Julia B.; Wojta, Johann; Yeghiazaryan, Lusine; Krall, Christoph; Palme, Rupert; Kleindorfer, Sonia; Plasenzotti, Roberto; Pollak, Daniela D.; Tillmann, Katharina E. (Frontiers in Behavioral Neuroscience, 2022)
Hygiene management protocols in laboratory mouse husbandries worldwide most commonly employ soiled bedding-exposed sentinel mice to monitor the occurrence of infections in mouse colonies. Using this approach, sentinel mice repeatedly receive a mixture of used bedding, supplied by a variety of cages of a defined hygienic unit for a period of several months. Hereby, microorganisms shed in the used bedding can infect the sentinel animals and be detected in subsequent health monitoring procedures. However, murine excrements carry more than only microorganisms. Mouse feces and urine also contain a multitude of olfactory molecules, which the animals use to code information about social status and context. However, if and how the persistent and repeated experience with these odor cues affects the behavior of sentinel mice, has not yet been explored. To address this question, we conducted a longitudinal study for neurochemical output parameters related to an organism´s responsiveness to challenging conditions, and for the exploratory assessment of a panel of home cage behaviors in soiled bedding and control mice with female C67BL/6J mice. We found that the number of mice showing abnormal repetitive behaviors, including barbering and bar mouthing, was lower in the soiled bedding group. While neutrophil/lymphocyte ratios and fecal corticosterone metabolites did not differ between groups, the within-group variance of the neutrophil/lymphocyte ratios was reduced in the soiled bedding group. These results show that that the occurrence of abnormal repetitive behaviors is lower in sentinel than in control mice and suggest a beneficial effect of soiled bedding on the welfare of laboratory mice and on outcome variability.